GE_GERICHTE P/18046/2012 vom 9. August 2016 - GE Cour de justice (2016)
PRÉSOMPTION D'INNOCENCE; LÉSION CORPORELLE GRAVE; INTENTION; DOL ÉVENTUEL; NÉGLIGENCE; LÉGITIME DÉFENSE; TORT MORAL | CP.122; CP.125; CP.47; CP.43; CPP.221; CPP.428; CPP.135; CO.47; CO.49